Impact of physical activity and psychological skills training with parental participation on cognitive, emotional, and behavioral outcomes in children with ADHD and their parents: A study protocol - Bumcheol Kim; Ejin Park; Jaewon Kim (PLoS ONE, 2025)
Background Attention Deficit/Hyperactivity Disorder (ADHD) is a neurodevelopmental disorder characterized by difficulties in attention, hyperactivity, and impulse control. Previous studies have suggested that engaging in moderate to vigorous physical activity (PA) and undergoing psychological therapy can help improve ADHD symptoms when combined with pharmacological treatments. This study aims to investigate the effects of parent participation in physical activities and psychological skills training (PST) on the cognitive, emotional, and behavioral outcomes of children with ADHD, as well as the emotional well-being of their parents. Methods Participants for the study will be recruited from a tertiary medical institution. The focus will be on children aged 6–12 years who have been diagnosed with ADHD and are currently receiving treatment at the hospital. Assessments will be conducted separately for the children and their parents. We will evaluate the children’s cognitive, emotional, and behavioral aspects, while for the parents, we will assess only emotional and behavioral aspects. The study will consist of three Intervention Groups (IG 1 and IG 2) and one control group. IG 1 will receive a combined intervention of PA and PST, IG 2 will participate in PA alone, and the control group will not receive any intervention. Discussion This study’s findings underscore the benefits of greater active participation when children participate in activities with their parents. It will also demonstrate the possible advantages of integrating PA with PST. The research will also explore how these interventions may influence parents, providing insights into whether their engagement enhances their psychological well-being. Trial registration This study is registered at Clinical Research Information Service (CRIS, https://cris.nih.go.kr) as KCT0010046